Maternal obesity impairs fetal brown adipogenesis by attenuating fetal FGF21 signaling - Lun Hua; Wenxue Shen; Dengfeng Gao; Yi Yang; Xiaohan Yang; Haoqi Zhang; Siyuan Liu; Luting Liu; Yaxue Cao; Xuemei Jiang; Xingfa Han; Chao Jin; et al. (Cell Reports)
Summary: In mammals, maternal obesity typically impairs brown adipose tissue (BAT) formation in fetuses, increasing their risk of metabolic disorders in adulthood. However, the mechanisms behind this phenomenon are not well understood. Our single-nucleus transcriptomic analysis revealed dynamic changes in cell heterogeneity within the fetal interscapular BAT (iBAT) from obese dams, leading to compromised thermogenesis in their offspring. Obese dams displayed elevated levels of circulating fibroblast growth factor 21 (FGF21), while their fetuses exhibited lower circulating FGF21 due to reduced trans-placental transfer. Maternal FGF21, significantly increased during late gestation, was the primary source of fetal FGF21, played a crucial role in regulating fetal brown adipogenesis, and likely prevented metabolic dysfunction in offspring. Additionally, the impaired iBAT development in utero due to maternal obesity could be mitigated by postnatal FGF21 supplementation. This study suggests that FGF21 signaling is a promising target for addressing impaired BAT development in fetuses resulting from maternal obesity.